Developing Young Learners’ EFL Writing Skills through a Pen Pal Telecollaboration Exchange during the Covid-19 Pandemic in Two Rural Institutions in Boyacá - Julieth Alejandra, Torres Beltrán; Santana Alarcón, Johana L. (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Eng: In language learning contexts, telecollaboration is understood as an exchange between people from different populations through the use of electronic means in order to develop intercultural and linguistic communication skills with the purpose of exchanging knowledge. In telecollaboration, bilingual models are proposed for learning a foreign language, on the one hand, this can be between students of different cultures, and on the other hand between students with a common language in order to strengthen the learning of another language. This study looked to promote telecollaborative exchange among 16 elementary school students in Boyacá aged between 9 to 11 years old. Considering the age of the participants and their needs, we sought to develop one of the production skills, in this case, writing, considered by the participants as the most complex. The objective of this project was to explore and describe young learners’ EFL writing skills development as they become involved in a telecollaboration exchange of personal letters during the pandemic between two institutions. The results showed a positive evolution in writing skills during the telecollaborative exchange as students expressed the emotions generated by the pandemic and their new friendship. This demonstrated that curiosity, motivation, diversity, confidence, and technological tools can transform foreign language learning in any context.